Interpreting the Outcomes of Automated Internet-Based Randomized Trials: Example of an International Smoking Cessation Study - Leykin, Yan; Aguilera, Adrian; Torres, Leandro D; Pérez-Stable, Eliseo J; Muñoz, Ricardo F (JMIR Publications, 2012)
BackgroundSmoking is one of the largest contributors to the global burden of disease. Internet interventions have been shown to reduce smoking rates successfully. However, improved methods of evaluating effectiveness need to be developed for large-scale Internet intervention trials. ObjectiveTo illustrate a method to interpret outcomes of large-scale, fully automated, worldwide Internet intervention trials. MethodsA fully automated, international, Internet-based smoking cessation randomized controlled trial was conducted in Spanish and English, with 16,430 smokers from 165 countries. The randomized controlled trial replicated a published efficacy trial in which, to reduce follow-up attrition, 1000 smokers were followed up by phone if they did not provide online follow-up data. ResultsThe 7-day self-reported abstinence rates ranged from 36.18% (2239/6189) at 1 month to 41.34% (1361/3292) at 12 months based on observed data. Given high rates of attrition in this fully automated trial, when participants unreachable at follow-up were presumed to be smoking, the abstinence rates ranged from 13.63% (2239/16.430) at 1 month to 8.28% (1361/16,430) at 12 months. We address the problem of interpreting results with high follow-up attrition rates and propose a solution based on a smaller study with intensive phone follow-up. ConclusionsInternet-based smoking cessation interventions can help large numbers of smokers quit. Large-scale international outcome studies can be successfully implemented using automated Internet sites. Interpretation of the studies' results can be aided by extrapolating from results obtained from subsamples that are followed up by phone or similar cohort maintenance methods. Trial RegistrationClinicalTrials.gov NCT00721786; http://clinicaltrials.gov/ct2/show/NCT00721786 (Archived by WebCite at http://www.webcitation.org/63mhoXYPw)